Prospects of Implementing Sustainable Architecture in Libya: A Field Study (Comprehensive Journal of Science, 2025)
The current situation in Libya, particularly in the aftermath of conflict and the onset of reconstruction and rehabilitation efforts, necessitates the design of engineering projects based on the latest technologies in the field of construction. Given the global shift toward the implementation of sustainable architecture standards—due to their profound impact on sustainable development—this study aims to elucidate the core concepts of sustainable architecture and examine its applicability in the Libyan context.The study seeks to evaluate a number of sustainable architectural technologies with the objective of adopting them in future reconstruction projects. It explores regional experiences to identify the most effective techniques implemented in neighboring countries. Based on this analysis, the technologies with the highest potential for successful application were identified and ranked in descending order according to scores assigned through a set of design, environmental, and implementation criteria. This process facilitates the formulation of a clear vision for the most promising sustainable technologies suitable for future engineering reconstruction initiatives.Furthermore, the study provides an analysis of the challenges hindering the adoption of sustainable architectural technologies in Libya, drawing from the perspectives of engineering institutions experienced in dealings with government agencies, suppliers, and project owners, as well as their familiarity with the costs and expenditures of engineering projects. Finally, the study offers a set of recommendations aimed at enhancing the integration and benefits of sustainable architectural elements
Keywords: Sustainable architecture, reconstruction, technologies.